Penerapan Sikap Duduk Ergonomis Dalam Pembelajaran Teknik Mengetik Cepat Pada Murid Kompetensi Keahlian Manajemen Perkantoran Dan Layanan Bisnis Di Smk Negeri 2 Sungailiat - Anik Setyowati; Rini Kusumawardani; Nur Qudus; Ade Novi Nurul Ihsani (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPLEMENTATION OF ERGONOMIC SITTING POSITION IN LEARNING FAST TYPING TECHNIQUES FOR OFFICE MANAGEMENT AND BUSINESS SERVICES COMPETENCY STUDENTS AT STATE VOCATIONAL HIGH SCHOOL 2 SUNGAILIAT Implementing a correct ergonomic sitting posture can help students feel more comfortable, reduce fatigue, and support concentration during speed typing lessons. However, 20 students, or 61%, still failed to apply ergonomic sitting postures correctly and consistently during speed typing practice. This study aimed to determine the general application of ergonomic sitting postures in speed typing lessons and to identify the steps teachers take in implementing ergonomic sitting postures in speed typing lessons for students in the Office Management and Business Services Competency (MPLB) at SMK Negeri 2 Sungailiat. The research design used was a qualitative descriptive study. The subjects in this study consisted of teachers who teach speed typing techniques in the MPLB Competency and 11th-grade students in the Office Management and Business Services Competency (MPLB). Triangulation was used to validate the data. The data analysis technique used was descriptive qualitative data analysis. The results showed: 1. The implementation of ergonomic sitting postures is not yet fully optimal. Some students still exhibit sitting habits that are not in accordance with ergonomic principles, such as hunching, positioning their heads too close to the monitor, or not maintaining correct posture during the practice. 2. The application of ergonomic sitting posture in learning fast typing techniques at SMK Negeri 2 Sungailiat has been implemented as part of the computer-based practical learning process. Teachers have directed students to apply the correct sitting position before and during the typing activity.